Management Mornings: A Strategic Tool for Organizational Progress - MohammadSadegh Abolhasani; Najmeh Baghian; Roohollah Askari (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat)
This study examines the necessity and methodology of implementing daily managerial briefing sessions (morning huddles) in healthcare organizations. Inspired by established clinical training practices, these sessions serve as a tool to improve inter-managerial communication, interdepartmental coordination, problem identification and resolution, enhance motivation and commitment, and ultimately elevate the quality of services provided. The paper emphasizes the importance of sharing experiences and knowledge, and proposes strategies for effective morning huddle implementation, including: setting clear objectives, ensuring regular and active participation of management team members, maintaining concise and productive sessions, utilizing active participation methods (such as brainstorming and quick polling), following up on outcomes and decisions, and conducting periodic evaluations for continuous process improvement. The findings of this study can assist healthcare managers in improving performance and enhancing service quality.